1970
DOI: 10.1159/000175302
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Effects of Dietary Rapeseed Oil in Rats

Abstract: The pathological effects of dietary rapeseed oil (RSO) in rats have been investigated. Rats given 60 cal% RSO for 2 weeks showed fatty accumulation in the heart, skeletal muscles and adrenals. In another experiment, 60 cal% RSO was given for 2, 4, 8 and 16 weeks. The fatty infiltration of the skeletal muscles, adrenals and hearts regressed with the increase in the dietary period, but in the heart, necrotic foci, aggregations of mono-nuclear cells, and an increase in the connective tissue elements ensued. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(77 citation statements)
references
References 11 publications
7
70
0
Order By: Relevance
“…Many studies regarding the effects of rapeseed oil-enriched diets on membrane composition and function (Dewailly et al 1977;Innis and Clandinin 1981a, b;Renner et al 1979) were triggered by the correlation between longtime exposure to these diets and rat heart lesions, including necrotic foci, aggregations of mononuclear cells and an increase in the connective tissue elements. These adverse effects were attributed to erucic acid, a major constituent in rapeseed oil (Abdellatif and Vles 1970). Interestingly, other studies point exactly in the opposite direction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies regarding the effects of rapeseed oil-enriched diets on membrane composition and function (Dewailly et al 1977;Innis and Clandinin 1981a, b;Renner et al 1979) were triggered by the correlation between longtime exposure to these diets and rat heart lesions, including necrotic foci, aggregations of mononuclear cells and an increase in the connective tissue elements. These adverse effects were attributed to erucic acid, a major constituent in rapeseed oil (Abdellatif and Vles 1970). Interestingly, other studies point exactly in the opposite direction.…”
Section: Discussionmentioning
confidence: 96%
“…The relevance of this oil on human nutrition has increased remarkably in the last decades, representing 15 % of world vegetable oil production in 2008, just behind palm oil and soybean oil (Rosillo-Calle et al 2009). The interest on the use of rapeseed oil in this context arose from the observation that heart pathological lesions took place after longtime dietary exposure to that oil (Abdellatif and Vles 1970). Bioenergetic studies revealed that the efficiency of rat heart mitochondria to oxidize substrates was substantially lowered when rapeseed oil was incorporated in the diet (Houtsmuller et al 1970).…”
Section: Introductionmentioning
confidence: 99%
“…EA causes a transient lipidosis and dilated cardiomyopathy in several species and is associated with an elevation in hepatic triglycerides after long-term feeding in rats ( 30 ). However, mice are resistant to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, when rats were fed on a diet containing 9.2Cal% erucic acid for 2 weeks, only minor fatty infiltration of the heart and skeletal muscles was observed (15). Erucic acid having no significant influence was also reported in myocardial lesions when rats were fed for 16 weeks on commercial lard to which 5.4% erucic acid was added (16).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researches on fat metabolism have come to suggest some possible adverse effects of erucic acid in the diet (14)(15)(16). However, when rats were fed on a diet containing 9.2Cal% erucic acid for 2 weeks, only minor fatty infiltration of the heart and skeletal muscles was observed (15).…”
Section: Discussionmentioning
confidence: 99%